2010
DOI: 10.1021/ef901136r
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of Polychlorodibenzodioxin/Furans (PCDD/Fs), Dioxin-Like Polychlorinated Biphenyls (PCBs), Polycyclic Aromatic Hydrocarbons (PAHs), and Volatile Compounds Produced in the Combustion of Pine Needles and Cones

Abstract: Emission factors of carbon oxides, light hydrocarbons, polycyclic aromatic hydrocarbons (PAHs), polychlorodibenzodioxin/furans (PCDD/Fs), and dioxin-like polychlorinated biphenyls (PCBs) were determined in the combustion of a mixture of pine needles and cones in a residential stove. Furthermore, several combustion experiments were carried out in a laboratory-scale reactor: pine needles were burnt at 500 and 850 °C, and pine cones were burnt at 500 and 850 °C. In the laboratory reactor, combustion at 500 °C yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…40 Additionally, decreased PAH emissions to the atmosphere were reported for high temperature burning in laboratory combustion studies. 41,42 Zhang et al 41 also found lower ∑ 16 PAH emissions during combustion of agricultural crop residues at higher burn intensities. Similarly, Molto et al 42 found decreased ∑ 16 PAH yields from pine needles and cones when the burn temperature increased from 550 to 850 °C.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…40 Additionally, decreased PAH emissions to the atmosphere were reported for high temperature burning in laboratory combustion studies. 41,42 Zhang et al 41 also found lower ∑ 16 PAH emissions during combustion of agricultural crop residues at higher burn intensities. Similarly, Molto et al 42 found decreased ∑ 16 PAH yields from pine needles and cones when the burn temperature increased from 550 to 850 °C.…”
Section: Resultsmentioning
confidence: 93%
“…41,42 Zhang et al 41 also found lower ∑ 16 PAH emissions during combustion of agricultural crop residues at higher burn intensities. Similarly, Molto et al 42 found decreased ∑ 16 PAH yields from pine needles and cones when the burn temperature increased from 550 to 850 °C. Although ∑ 16 PAH concentrations showed no significant difference (p = 0.06) between W-Ash and the nonburned soils in this study, the average ∑ 16 PAH concentration in W-Ash was about two times higher than the nonburned soils with a p-value (0.06) approaching our significance threshold (p ≤ 0.05).…”
Section: Resultsmentioning
confidence: 93%
“…Table 5 shows a comparison of the yields of PCDD/Fs and PCBs obtained in the combustion of other samples in the same laboratory reactor and the same residential stove. Pine needles and cones 0.12 175 Moltó et al (2010) The presence of metals in the fuel increases the levels of PCDD/Fs generated, as can be observed in Table 5 comparing the emissions of PCDD/Fs from the combustion of sewage sludge with high metal content and sewage sludge with low metal content. Levels of PCDD/Fs obtained in the combustion of furniture wood waste are lower than those obtained in the combustion of sewage sludge (with high and low metal content) and biomass (such as needles and cones of pine).…”
Section: Resultsmentioning
confidence: 95%
“…Moltó et al carried out an experiment involving burning tomato plants in a laboratory reactor at 500°C and in a home furnace at 220°C. The amount of PCBs produced in the exhaust gases was measured, and the following results were obtained for the reactor: 3284.46 ng/kg of biomass and 1.68 ng/kg of burnt biomass for the household stove [ 20 ]. The above studies illustrate that despite the lack of PCBs in waste, PCBs can be formed when various wastes are incinerated.…”
Section: Introductionmentioning
confidence: 99%